PROPAGATION OF THE ‘NIAGARA ROSADA’ GRAPEVINE (vitis labrusca) GRAFTED ON THE ROOTSTOCK ‘VR-043-43’ (V. vinifera x V. rotundifolia) - BOTELHO, Renato Vasconcelos; SOUZA, Joacir; SCHREIDER, Everton; PIRES, Erasmo José Paioli; TERRA, Maurilo Monteiro (Scientia Agraria, 2009)
Aiming to develop a technology of nursery trees production of grapevines cv. Niagara Rosada graft on rootstock ’VR-043-43’, a trial was carried out in nursery conditions. The following treatments were used: T1 – herbaceous cuttings planted in January of 2006 and grafted in September of 2006 (winter grafting); T2 – Woody cuttings planted and grafted simultaneously in September of 2006 (winter grafting); T3 – Herbaceous cuttings planted in January of 2006 and grafted on December of 2006 (green grafting); T4- Herbaceous cuttings planted and grafted simultaneously in march of 2007 (green grafting). 90 days after grafting, the following variables were evaluated: percentage of survivation, mean length scion shoot and diameter of shoot base. For the variables percentage survivation and diameter of shoot base, the best results were verified for the cuttings rooted in January (midsummer) and winter grafting in September. Nevertheless, this treatment attained only 43% of survivation, probably due to the reduced cuttings size. In relation to the grafting methods, the modified cleft method outstood for the variables length and diameter of shoot scion. For the variable percentage of survivation, no differences were verified between grafting methods.